High intratumoral dihydrotestosterone is associated with antiandrogen resistance in VCaP prostate cancer xenografts in castrated mice - Huhtaniemi Riikka; Sipilä Petra; Junnila Arttu; Oksala Riikka; Knuuttila Matias; Mehmood Arfa; Aho Eija; Laajala Teemu D.; Aittokallio Tero; Laiho Asta; Elo Laura; Ohlsson Claes; et al. (Elsevier Inc., 2025)
Antiandrogen treatment resistance is a major clinical concern in castration-resistant prostate cancer (CRPC) treatment. Using xenografts of VCaP cells we showed that growth of antiandrogen resistant CRPC tumors were characterized by a higher intratumor dihydrotestosterone (DHT) concentration than that of treatment responsive tumors. Furthermore, the slow tumor growth after adrenalectomy was associated with a low intratumor DHT concentration. Reactivation of androgen signaling in enzalutamide-resistant tumors was further shown by the expression of several androgen-dependent genes. The data indicate that intratumor DHT concentration and expression of several androgen-dependent genes in CRPC lesions is an indication of enzalutamide treatment resistance and an indication of the need for further androgen blockade. The presence of an androgen synthesis, independent of CYP17A1 activity, has been shown to exist in prostate cancer cells, and thus, novel androgen synthesis inhibitors are needed for the treatment of enzalutamide-resistant CRPC tumors that do not respond to abiraterone.